PENGEMBANGAN MODUL KONTEN HYPER TERCETAK UNTUK SUBYEK KEPEMIMPINAN - Hendri Eka Jaya Putra; Robinson Situmorang; Suyitno Muslim (Akademika : Jurnal Teknologi Pendidikan, 2020)
This research produces a printed module for hypertcontent leadership subjects. The methodology used is Research and Development (R & D) research, in its development this research uses the Rowntree model. Hypercontent printed module combines hypertext, hypertmedia and hypertlink into one part that can enrich the content of the material in this print module, to be able to access material online using QR-Code.There are three stages in this research, namely (1) the planning stage, (2) the writing preparation stage, (3) the writing and editing stage (Rowntree, 1994) . The results of the validation by the experts showed that the average material expert test was 3.43 and the media and instructional experts were 3.14. Furthermore, after repairing the product, an individual trial was carried out involving 3 respondents using the face to face method, the average was 3.39, and regarding to (Hake, 1998) the effectiveness test with the N-Gain score was obtained a score of 0.72 (72%) , this means that the hypercontent print module developed very effective. The conclusion from the results of this study shows that the hypercontent print module is already good, thus the hypercontent print module for leadership subjects is suitable for learning at Fitrah Islamic World Academy Bogor High School.